Drivkrafter och barriärer för Green supply chain management inom offentliga organisationer - Haglund, Linnéa; Karlsson, Malin (SLU/Dept. of Economics, 2010)
The purpose of this paper is to analyze the driving forces and barriers which may exist at the implementation of green supply chain management (GSCM) within public organizations. Suggestions that may increase or reduce driving forces and barriers to public activities will also be provided, where such is found. The background of the study is that the public sector is such a major customer for many companies / providers, which makes the sector able to highly affect its suppliers. This essay is based on literature studies. The results showed that GSCM is a relatively unexplored area, especially applied on the public sector. Because of this, scientific assumptions have been made, with the help of general GSCM models which has been applied to public organizations. The conclusion is that the driving forces that can be applied to public organizations in particular, are the organization's desire to reduce costs, desire to reinforce / gain legitimacy, pressure from society, regulations and pressure from investors. The barriers that can be linked to public sector organizations are the risk of reduced legitimacy, lack of environmental information, knowledge and training, and regulations.